Effect of organic acids on bread quality improvement - Su, Xueqian; Wu, Fengfeng; Zhang, Yuqing; Yang, Na; Chen, Feng; Jin, Zhengyu; Xu, Xueming (Food chemistry, 2019)
•The acidified bread showed higher volume, lower moisture content and lower hardness.•Gluten network weakened and yeast activity enhanced in chemical acidified doughs.•Proteins and starches in acidified doughs showed varying degrees of hydrolysis.•Hydrolysis of proteins and starches mainly occurred after dough mixing.•Proteolysis and amylolysis basically depended on types of organic acids. This study aimed to improve the bread quality by adding acetic acid, lactic acid, malic acid, fumaric acid and citric acid to its ingredients. The underlying mechanism was explored through the changes in the yeast activity, proteolysis and amylolysis. All organic acids gave bread a higher specific volume, a lower moisture content, a lower pH value and a decreased hardness. Moreover, the yeast activity was enhanced, whereas the gas retention capability decreased in acidified doughs. Organic acids also reduced the molecular weight of proteins and starches, which led to the increase of NH2, free SH and reducing sugar contents. These changes were the most significant in the dough with 0.3% fumaric acid. Proteolysis and amylolysis mainly occurred after dough mixing and depended on the types of acids present in the mixture. Nevertheless, the cleavage of disulfide bonds in gluten might rest with the H+ concentration in the dough system.